Extraordinary Endeavours Of Helen Keller In Helen Keller's The Story Of My Life (1903): An Individual Psychological Approach - WATI, SETYO (2012)
This research represents the result summary depicting an individual psychological criticism which is included in a novel entitled The Story of My Life by Helen Keller. This paper elaborates the extraordinary endeavours of Helen Keller reflected in the novel that are analyzed through individual psychological approach. The research result is that the personality of Helen Keller is influenced by her inferiority feelings of her physical lacks to strive for superiority to limit her boundaries by using her extraordinary endeavours. The basic principles of an Individual Psychology construct a unity viewed from Helen's personality to penetrate her boundaries.